Coordination polymers with free Brønsted acid sites for selective catalysis. (10th December 2014) - Ma, Lu-Fang; Shi, Zhen-Zhen; Li, Fei-Fei; Zhang, Jian; Wang, Li-Ya
Abstract : The Cu(ii ) coordination polymers with free –COOH groups as Brønsted acid sites show high activity and regioselectivity in catalyzing epoxide ring-opening reactions. Abstract : By employing the 5-nitro-1, 2, 3-benzenetricarboxylate ligand, two Cu(ii ) coordination polymers with free –COOH groups as Brønsted acid sites are synthesized, and both compounds show high activity and regioselectivity in catalyzing epoxide ring-opening reactions.